2017
DOI: 10.1111/ibi.12454
|View full text |Cite
|
Sign up to set email alerts
|

Strong territoriality and weak density‐dependent reproduction in Lesser Spotted Eagles Clanga pomarina

Abstract: We assessed whether populations of the migratory, philopatric, territorial Lesser Spotted Eagle Clanga pomarina are regulated through territoriality and density‐dependent reproduction rates. In the north‐western part of the distribution to the east of the Baltic Sea, territories were spaced regularly and consistently between years. We did not find strong support for an improvement of reproductive output with an increase in distance to the nearest neighbour or with a decrease of the number of conspecifics withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The most influential study to examine NND avg described a case study that found enhanced breeding parameters were associated with synchronicity and super abundance of their main prey ( Mycrotus spp. ; Treinys, Bergmanis & Väli, 2017 ), thus supporting the resource availability-territory size hypothesis. On the other hand, the Golden eagle ( A. chrysaetos ) was the only species to have a greater NND than expected.…”
Section: Discussionsupporting
confidence: 65%
“…The most influential study to examine NND avg described a case study that found enhanced breeding parameters were associated with synchronicity and super abundance of their main prey ( Mycrotus spp. ; Treinys, Bergmanis & Väli, 2017 ), thus supporting the resource availability-territory size hypothesis. On the other hand, the Golden eagle ( A. chrysaetos ) was the only species to have a greater NND than expected.…”
Section: Discussionsupporting
confidence: 65%
“…Even if an improvement is expected after that, the populations of species depending on the targeted habitat may not recover and local or regional extinction risks can be expected to increase (e.g., Reference [34]). The long-term population persistence in the landscapes may be at risk, especially for species with low reproduction rate and strong philopatry, for example the Lesser Spotted Eagle [81]. Moreover, most of the tree nesting raptors in Lithuania prefers older forests as breeding territory [59] and nest site level [75,77].…”
Section: Discussionmentioning
confidence: 99%
“…We chose NND because studies exploring different measurements found the distance to nearest neighbours to be the best predictor for density dependence (e.g. [63]).…”
Section: Plos Onementioning
confidence: 99%